2012
DOI: 10.1007/s11481-012-9362-3
|View full text |Cite
|
Sign up to set email alerts
|

D1/NMDA Receptors and Concurrent Methamphetamine+HIV-1 Tat Neurotoxicity

Abstract: The interactive effects of HIV-1 infection and methamphetamine (METH) abuse in producing cognitive dysfunction represent a serious medical problem; however, the neural mechanisms underlying this interactive neurotoxicity remain elusive. In this study, we report that a combination of low, sub-toxic doses of METH + HIV-1 Tat 1–86 B, but not METH + HIV-1 gp120, directly induces death of rodent midbrain neurons in vitro. The effects of D1- and NMDA-receptor specific antagonists (SCH23390 and MK-801, respectively) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 75 publications
0
15
0
Order By: Relevance
“…It has been shown that Meth accelerates HIV infection and synergistically potentiates gp120- and Tat-associated neurotoxicity (Maragos et al, 2002; Nair et al, 2009; Nair and Samikkannu, 2012; Silverstein et al, 2012; Turchan et al, 2001). Multiple mechanisms for Meth-induced potentiation have been proposed including upregulation of HIV-1 co-receptors CXCR4 and CCR5 expression (Nair and Saiyed, 2011; Nair et al, 2009), interaction with NMDA receptors producing excitotoxic neural injury (Aksenov et al, 2012), oxidative stress (Purohit et al, 2011; Shah et al, 2013), and disruption of dopaminergic function (Aksenov et al, 2012; Purohit et al, 2011) and the blood-brain barrier (Mahajan et al, 2008). In this study, we found that Meth and gp120 enhance microglial expression of K v 1.3 channel protein and outward K current leading to an increased microglial production of TNFα, IL-1β, and NO and resultant enhancement of microglial neurotoxic activity.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that Meth accelerates HIV infection and synergistically potentiates gp120- and Tat-associated neurotoxicity (Maragos et al, 2002; Nair et al, 2009; Nair and Samikkannu, 2012; Silverstein et al, 2012; Turchan et al, 2001). Multiple mechanisms for Meth-induced potentiation have been proposed including upregulation of HIV-1 co-receptors CXCR4 and CCR5 expression (Nair and Saiyed, 2011; Nair et al, 2009), interaction with NMDA receptors producing excitotoxic neural injury (Aksenov et al, 2012), oxidative stress (Purohit et al, 2011; Shah et al, 2013), and disruption of dopaminergic function (Aksenov et al, 2012; Purohit et al, 2011) and the blood-brain barrier (Mahajan et al, 2008). In this study, we found that Meth and gp120 enhance microglial expression of K v 1.3 channel protein and outward K current leading to an increased microglial production of TNFα, IL-1β, and NO and resultant enhancement of microglial neurotoxic activity.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a recent study reveals that D1R expression is significantly increased in the brain of HIV-1 Tg rats [73]. Further, death of midbrain dopaminergic neurons induced by Tat, as well as by combined sub-toxic doses of Tat and methamphetamine, is attenuated by inhibition of D1Rs [74, 75]. Because D1R activation facilitates the cAMP/PKA cascade, it is possible that increased D1R expression in HIV-infected brains may lead to enhanced phosphorylation of NMDAR, thereby inducing additional increase of Ca 2+ influx in neurons.…”
Section: Tat-mediated Dysregulation Of Ca2+ Influx and [Ca2+]in: Mmentioning
confidence: 99%
“…Tat has been shown to activate glutamatergic NMDA receptors (NMDARs) through a variety of direct and indirect mechanisms (Magnuson et al, 1995;Haughey et al, 2001;Pérez et al, 2001;Li et al, 2008;Aksenov et al, 2012). Tat mediates neurotoxic glutamate release, which activates AMPA receptors (AMPARs) that can upregulate NMDA-mediated toxicity (Longordo et al, 2006), leading to dendritic structural and functional defects observed in HIV-1 infected individuals (Mattson et al, 2005).…”
Section: Introductionmentioning
confidence: 99%